Calculation of Modes Properties for Single-Mode and Multimode Fibers at 633 nm - M. Hmood, Wasan; Salih, Aqeel R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The need for optical fibers has emerged for its ability to transmit information with less attenuation and over long distances. In this work, four optical fibers with core radii from 1 μm to 4.75 μm in steps of 1.25 μm and a numerical aperture of 0.17 were studied and their modes properties have been calculated at a wavelength of 633 nm by using RP Fiber Calculator (free version 2022). Also, the effect of increasing the core radius on these properties has been studied. Multimode fibers can be obtained when the radius of the fiber core is large compared to the operating wavelength of the fiber which is less than the cutoff wavelength of the mode. Otherwise, a single-mode fiber is obtained. It has been concluded that all the calculated properties increase with increasing core radius. More than half of the power is contained in the core. Intensity profiles of all modes were illustrated.